Synaptic response in organic electrochemical transistor gated by a graphene electrode. (1st November 2019) - Battistoni, Silvia; Peruzzi, Carlotta; Verna, Alessio; Marasso, Simone L; Cocuzza, Matteo; Erokhin, Victor; Iannotta, Salvatore
Abstract: The volatile nature of current variations in organic electrochemical transistors (OECTs) is limiting their use in neuromorphic applications that demand not only temporary variations but also permanent modifications of the resistance states. Only a limited number of papers report on OECTs modified to achieve memristive/synaptic properties. Here we report a novel approach developed using standard OECTs combined with a graphene film as a gate electrode. We demonstrate that the proposed architecture could be optimized to achieve typical and unique non-volatile characteristics with neuromorphic-synaptic functionalities.